Molecularly imprinted fluoroprobes doped with Ag nanoparticles for highly selective detection of oxytetracycline in real samples - Wang Jixiang; Zou Lihua; Xu Jingjing; Zhang Rong; Zhang Hongbo (ELSEVIER, 2022)
A molecularly imprinted polymer (MIP), which is synthesized by a nanomolding process around a template, has emerged as a promising analytical tool for environmental quality monitoring and food safety test.In this work, a fluoroprobe with Ag-doped MIP nanolayer (16 nm thickness) is successfully prepared for the highly selective detection of oxytetracycline (OTC) in real samples (i.e. Yangtze River water, swine urine). In the MIP nanolayer, two functional monomers (i.e. 4-(2-acrylamidoethylcarbamoyl)-3-fluorophenylboronic acid, methacrylic acid) synergistically constitute the specific recognition sites. Meanwhile, the doped Ag enhances the detection sensitivity (with a detection limit of 5.38 nM) and accelerates the detection rate (within 2.5 min) even in real samples. Therefore, the present study paves the way for the preparation of MIP-based fluoroprobes, showing great prospects in environmental quality and food safety tests.(c) 2021 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).